A study of the relationship between empowerment and creativity of workers in Algerian institutions: case study of a sample of workers of the Algerian Directorate of Telecom in Laghouat - Cheteha, Aicha; Ben khlifa, Fatima Alzahraa (Dirassat Journal Economic Issue, 2018)
his study aims to clarify the role of empowerment in the development of creativity among employees, through highlighting the contemporary administrative concept of empowerment supported by organizations and adopted by the management strategy in order to achieve goals more efficiently and effectively, in addition to briefing the subject of creativity and the pursuit of organizations to develop and get interested in it as a way to lead in the business world. Also, it has been dropped what has been presented in the theoretical side in the practical directorate of Algeria Telecom institution (Laghouat), and we have based to achieve this on a questionnaire which was distributed to a random sample of workers in the organization estimated (53) person, in addition to an interview with the heads of departments and services. After the analysis of data collected using statistical methods with the program Spss19 and Excel 2007, we came to a set of conclusions and recommendations, and it was the most important: the direction of the sample towards the approval of the existence of empowerment organization despite the absence of participating in decision-making, work teams, training, effective communication, motivation, efficiency and competence, also the sample turned towards accepting the existence of creativity among workers. To arrive in the latter that there is a direct correlation statistically significant between the empowerment and development of creativity among workers in the practical directorate of Algeria Telecom (Laghouat) at the level of significance (5%), and the study concluded a series of recommendations, including: the need to activate empowerment in the nominally six, namely: participation in decision making, work teams, training, effective communication, motivation, efficiency and competence. addition to working to strengthen a culture of empowerment and creativity in the enterprise.